Unaffordable Housing and Local Employment Growth: Evidence from California Municipalities - Ritashree Chakrabarti; Junfu Zhang (Institute for the Study of Labor (IZA), 2014)
It is widely believed that unaffordable housing could drive businesses away and thus impede job growth. However, there is little evidence to support this view. This paper presents a simple model to clarify how housing affordability is linked to employment growth and why unaffordable housing could negatively affect employment growth. The paper then investigates this effect empirically using data on California municipalities. For various reasons, a simple correlation between unaffordable housing and employment growth cannot be interpreted as causal. Several empirical strategies are employed to identify the causal effect of unaffordable housing on employment growth. The estimation results provide consistent evidence that unaffordable housing indeed slows local employment growth. Policy implications of these findings are briefly discussed.
Keywords: R11; R12; R13; 330; amenity; employment growth; housing affordability; California